A Scalable H2O–DMF–DMSO Solvent Synthesis of Highly Luminescent Inorganic Perovskite‐Related Cesium Lead Bromides. Issue 3 (2nd December 2020) - Zhou, Bo; Ding, Dong; Wang, Ye; Fang, Shaofan; Liu, Zexiang; Tang, Jian; Li, Henan; Zhong, Haizhe; Tian, Bingbing; Shi, Yumeng
Abstract: All‐inorganic cesium lead bromide perovskites have attracted a lot of attention because of their excellent optical properties that can potentially be applied in various optical devices. However, large‐scale preparation of cesium lead bromide perovskites with outstanding optical performance is still hindered by the poor solubility of CsBr in polar aprotic solvents. In this work, a water/dimethylsulfoxide (DMSO)/dimethylformamide (DMF) system is demonstrated for the synthesis of inorganic cesium lead bromide perovskites, where the introduction of water can effectively address the dissolution issue of Cs + ions. Large‐scale synthesis of pure‐phase emissive Cs4 PbBr6 with a product yield of up to 73% is achieved and the photoluminescence quantum yield of resulting product reaches as high as 76%. The origin of the light emission is further revealed by the photoluminescence evolution of the colored Cs4 PbBr6 single crystals. Furthermore, reversible phase transitions between Cs4 PbBr6, CsPbBr3 and CsPb2 Br5 are achieved by changing solely the water content, which paves the way for the recycle of the mother solution of Cs4 PbBr6 without generation of additional hazardous waste. The three‐solvent‐based synthetic approaches enable an economical, robust, and large‐scale production for all‐inorganic cesium lead bromide perovskites. Abstract : Reversible phase transitions between Cs4 PbBr6, CsPbBr3 and CsPb2 Br5 can be controlled by varying the amount of water and dimethylsulfoxide (DMSO) in the water–dimethylformamide (DMF)–DMSO system. Compared with the traditional anhydrous DMF/DMSO system, the three‐solvent system provides an ideal solution environment for the direct growth of pure‐phase emissive Cs4 PbBr6 crystals without going through the CsPbBr3 intermediate phase.